Beziehungen zwichen Abfluss und Ionengehalt in kleinen Einzugsgebieten des Südniedersächsischen Berglandes - Pörtge, Karl-Heinz; Rienäcker, Ingolf (ERDKUNDE, 1989)
The relations between material concentration and run off were investigated in 12 catchments in the southern Leine-Weser-mountain region. The 12 catchments were free of settlements and differently used. The data obtained were compared. The dissolved material of the run-off consists of alkaline earth, mostly hydrogenic-carbonatic, and sometimes of sulphatic constituents. The rate of mineralization runs from 1.7 up to 20.5 mmol/1 (eq), depending on the lithogenous situation of the catchment. The mostly geogenic substances, such as Ca, Mg, HC03, and in part S04, have minimum variability and are subject to the so-called dilution effect at increasing run-off rates. Species such as K, P04, NH4,N03, and the atmogenic S04 show bigger fluctuations in the flow regime and their content usually correlates positively with the run-off. The relation between ion content and run-off is to be evaluated specifically in each area because the dilution effect of the element concentration during increasing run-off was not observed in all cases.